Association between treatment delays and oncologic outcome in patients treated with surgery and radiotherapy for head and neck cancer. Issue 2 (13th December 2018) - Tumati, Vasu; Hoang, Lawrence; Sumer, Baran D.; Truelson, John M.; Myers, Larry L.; Khan, Saad; Hughes, Randall S.; Nedzi, Lucien; Sher, David J.
Abstract: Background: This study sought to determine the oncologic impact of delays to surgery, radiotherapy, and completion of therapy in patients with head and neck squamous cell carcinoma. Methods: The impact of biopsy to surgery (BTS) time, surgery to start of radiation time (STSR), and radiation treatment time (RTT) on locoregional recurrence (LRR), distant metastases (DMs), and cancer‐specific mortality (CSM) was examined. The cumulative incidences (CI) of LRR, DMs, and CSM were examined using Fine–Gray testing. Results: A total of 277 patients treated with surgery and adjuvant radiotherapy were analyzed. On multivariable testing, BTS >50 days was associated with DM ( P  = .03), whereas RTT and STSR were not. RTT >43 days was associated with LRR ( P  = .02) in patients with non‐p16‐positive‐oropharynx cancer. Conclusions: An increase in DM appears to be the mechanism by which prolonged time to treatment initiation leads to worse overall survival. Prolonged RTT has the greatest impact on patients with non‐p16 positive oropharynx cancers.